Social Skills : learning cycle model and student team achievement divisions (STAD) - Hadis Aditia Muslim; M. Japar; Durotul Yatimah; Fitriyani Fitriyani (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2021)
This study aims to determine the effect of the Learning Cycle learning model and motivation to improve the social skills of elementary school students. This study used the STAD learning model treatment and the Learning Cycle learning model carried out in two different schools with 32 students of each school's research subjects and with the same level, namely the fourth grade of elementary school. Research method This research uses experimental research design with treatment by level 2x2 design, with the dependent variable in this study is social skills while the independent variable is the learning model with learning motivation. The treatment variables are divided into two, namely the learning cycle learning model and the student teams achievement divisions (STAD) learning model and the high learning motivation variable and low learning motivation. The results of this study indicate that there are differences in the social skills of elementary school students between students learning with the Learning Cycle Model and students learning using the Student Teams Achievement Divisions Model.